Pembuatan Pestisida Nabati Sebagai Solusi Pengurangan Pestisida Kimia Dalam Mengendalikan Organisme Pengganggu Tanaman - Sesarius Saves; Anastasia Bajar; Maria Elfrida Ujeng; Margareta Desiana Alus; Polikarpus Payong (STMIK Royal, 2023)
Abstrak: Farmers in Pau Village mostly use chemical pesticides. Many farmers have not used plant-based pesticides to control pests on the plants they cultivate. This condition is of concern to us to produce plant-disturbing organisms (OPT) on farmers' crops in Ruteng City. The purpose of this activity is to produce vegetable pesticides as environmentally friendly plant pest control. The method used in this activity is the demonstration method, which means directly processing and applying vegetable pesticides on farmers' land. The result of this activity is the product of the vegetable pesticide